Penerapan Ipteks Undang-Undang Nomor 1 Tahun 2022 Tentang Hubungan Keuangan Antara Pemerintah Pusat dan Pemerintahan Daerah - Katjong, Kadir; Yanuaria, Tri; Polontoh, Herry M.; Mulyadi, Dudi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
The capacity building of employees at the Regional Revenue Agency (Bapenda) of Jayapura Regency in understanding and implementing Law Number 1 of 2022 on Financial Relations between the Central Government and Regional Governments is crucial for optimizing regional financial management. This new regulation brings significant changes in the mechanisms of fund transfers, as well as tax and regional retribution management, requiring deep understanding and technical skills from the employees. The purpose of this community service is to enhance the understanding and skills of Bapenda Jayapura Regency employees in drafting academic papers and regional regulations (Raperda) related to taxes and retributions. Thus, it is expected to improve the effectiveness and efficiency of regional revenue management in accordance with the provisions of the new law. This community service is conducted using lecture and mentoring methods. The lecture method is used to provide theoretical understanding of Law Number 1 of 2022 and its implications for regional governments. Meanwhile, the mentoring method is used to assist employees in directly drafting academic papers and Raperda, ensuring that these documents comply with legal principles and local needs. The results of the community service show a significant increase in employees' understanding of the new financial regulations. Bapenda Jayapura Regency employees successfully drafted academic papers and Raperda on taxes and retributions in accordance with the provisions of Law Number 1 of 2022. Additionally, this activity also encouraged collaboration and interactive discussions that enriched the practical and theoretical understanding of the employees.